Significance of soluble intercellular adhesion molecule-1 and procalcitonin in diagnosis of neonatal septicemia - Ma, Li (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2004)
OBJECTIVE: Neonatal septicemia is a critical disease in neonatal period. Its incidence among live births is between 1 per thousand and 8 per thousand. Mortality of neonatal septicemia may be as high as 50% for infants who are not treated. The early signs of septicemia in the newborn are generally nonspecific. Blood culture and the other clinical diagnostic measures are not sufficiently sensitive. The present study aimed at evaluating potential use of soluble intercellular adhesion molecule-1 (sICAM-1), procalcitonin (PCT) and C-reactive protein (CRP) in diagnosis of septicemia